Essences et lois d’essence dans l’eidétique descriptive de Edmund Husserl - Rochus Sowa (Methodos, 2009)
Husserl’s transcendental phenomenology which he characterized as an eidetic science of transcendentally reduced phenomena aims at least at material-apriori laws of a special kind, namely eidetic descriptive laws built up from pure descriptive concepts. The paper explicates Husserl’s notion of essence in the broad sense as a state-of-affairs-function (Sachverhaltsfunktion) ; this noematic function is the objective “correlate” of the propositional function which we call a “concept” and which is part of the proposition, i.e. the state-of affairs-meaning (Sachverhaltsmeinung), in which a state of affairs is projected. Essences in the narrow or pregnant sense are pure essences which Husserl named “Eidé”. The concept of pure essence relevant for the phenomenological descriptive eidetics is elucidated through the explication of Husserl’s notion of a pure descriptive concept, so as to show how these concepts, which are pure type concepts, differ from impure descriptive concepts, especially from concepts denoting natural kinds. Grounded exclusively in pure descriptive concepts, the eidetic descriptive laws (Wesensgesetze) have special truth conditions and a need for special ways of examination. The proper place of the method called “eidetic variation” is the examination, falsification or justification of presumed eidetic descriptive laws. Starting from familiar exemplary cases of states of affairs which confirm the presumed law, the free variation, which operates in pure fantasy, has the task of constructing possible counterexamples to falsify the presumed eidetic law. The property of being falsifiable by counterexamples constructed in pure fantasy allows for a distinction between empirical laws and the eidetic descriptive laws of Husserlian eidetics. The falsifiability by fictional and factual counterexamples shows that Husserl’s transcendental phenomenology is a scientific enterprise open to intersubjective examination precisely due to its eidetic character.